Influence of buccal cusp reduction when using porcelain laminate veneers in premolars. A comparative study using 3-D finite element analysis - Archangelo, Carlos Marcelo; Rocha, Eduardo Passos [UNESP]; Anchieta, Rodolfo Bruniera [UNESP]; Martin, Manoel; Freitas, Amilcar Chagas [UNESP]; Ko, Ching-Chang; Cattaneo, Paolo M. (Japan Prosthodontic Society, 2011)
Objectives: Based on a maxillary premolar restored with laminate veneer and using the 3-D finite element analysis (FEA) and mCT data, the aim of this study was to evaluate the influence of different types of buccal cusp reduction on the stress distribution in the porcelain laminate veneer and in the resin luting cement layer. Methods: Two 3-D FEA models (M) of a maxillary premolar were built from mCT data. The buccal cusp reduction followed two configurations: Mt-buccal cusp completely covered by porcelain laminate veneer; and Mp-buccal cusp partially covered by porcelain laminate veneer. The loading (150 N in 458) was performed on the top of the buccal cusp. The finite element software (Ansys Workbench 10.0) was used to obtain the maximum shear stress (σmax) and maximum principal stress (σmax). Results: The Mp showed reduced the stress (σmax) in porcelain laminate veneer (from-2.3 to 24.5 MPa) in comparison with Mt (from-5.3 to 27.4 MPa). The difference between the peak and lower stress values of σmax in Mp (-6.8 to 26.7 MPa) and Mt (-5.3 to 27.4 MPa) was similar for the resin luting cement layer. The structures not exceeded the ultimate tensile strength or the shear bond strength. Conclusions: Cusp reduction did not affect significant increase in σmax and τmax. The Mt showed better stress distribution (τmax) than Mp. © 2011 Published by Elsevier Ireland on behalf of Japan Prosthodontic Society.
Keywords: Dental ceramics; Finite element analysis; Laminate veneers; Numerical analyses; resin cement; comparative study; dental bonding; dental procedure; denture; finite element analysis; human; mechanical stress; physiology; premolar tooth; tensile strength; tooth prosthesis; Bicuspid; Dental Bonding; Dental Porcelain; Dental Stress Analysis; Dental Veneers; Finite Element Analysis; Humans; Resin Cements; Stress, Mechanical; Tensile Strength